ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR UNIT LATIHAN KERJA INDUSTRI (ULKI) PROVINSI KALIMANTAN BARAT - B11109147, DEVINA KARINAZATI (Jurnal Manajemen Update, 2014)
The main objective of this research is to find out and analyze the influence of organizational culture on employee performance the office of Unit Latihan Kerja Industri (ULKI) of West Kalimantan Province. A sample in research for around 43 employees and is a sample of saturated / the census. The form of this research is research survey, that is by using a questionnaire, interviews and study and engineering documentation as a source of collecting data. Techniques that we use is statistics descriptive analysis was to see the answers of respondents through a questionnaire. A method of analysis used in this research is simple, linear regression analysis using program spss. While a method of research that we use is a method of quantitative. Independent variable in this research is organizational culture ( x ) and variable dependent is the employee performance ( y ). After the results of research shows that the value of koefisen determination ( r square ) 65,4 % while the rest of 34.6 % affected by by other factors out research. And the results of hypothesis testing on the 5% significant level, the t-test results known to significantly influence the variable of organizational culture on employee performance the office Unit Latihan Kerja Industri (ULKI) of West Kalimantan Province with t count > t table ( 8,802 > 2,021 ) and sig t (0,000) < ? (0,05). Keywords: organizational culture, employee performance